ARTIFICIAL INTELLIGENCE AND ENVIRONMENT PROTECTION- LEGAL ASPECTS - Stanić, Miloš B; Galić, Borislav (Serbian political thought, 2025)
Society is undergoing rapid transformation, posing significant challenges to legal systems worldwide. A central aspect of this transformation is the development of artificial intelligence (AI). At the same time, the right to a healthy environment, guaranteed by the constitution worldwide, is a fundamental human right and concerns all citizens, because everyone affects the state of the environment. The authors in this paper, after introducing the concept of artificial intelligence itself, first deal with the current normative state of the art in this area, both at the level of international public law and at the level of domestic legal orders. After that, the importance of environmental protection, the legal framework for its protection, and the norms regarding the use of artificial intelligence in environmental protection are presented, with an appropriate conclusion.
Keywords: healthy environment; artificial intelligence; international public law; constitutional law; protection; legal framework